2022
DOI: 10.1016/j.ejmp.2021.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review on the benefit of patient protection shielding during medical X-ray imaging: Towards a discontinuation of the current practice

Abstract: Patient shielding during medical X-ray imaging has been increasingly criticized in the last years due to growing evidence that it often provides minimal benefit and may even compromise image quality. In Europe, and as also shown in a short assessment in Switzerland, the use of patient shielding is inhomogeneous. The aim of this study was to systematically review recent literature in order to assess benefits and appraise disadvantages related to the routine use of patient shielding. Methods: To evaluate benefit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 74 publications
1
5
0
2
Order By: Relevance
“…The study found that the strength of the safety culture appears to be an important factor influencing the likelihood of using gonad shielding. Use of gonad shielding has been a topic of debate among medical professionals in the field of radiology [17,18], and, just recently, a statement from the European professional societies on patient shielding was issued in which the recommendation was not to apply gonad shielding [19]. The Swedish Radiation Safety Authority has not yet changes their recommendations accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the strength of the safety culture appears to be an important factor influencing the likelihood of using gonad shielding. Use of gonad shielding has been a topic of debate among medical professionals in the field of radiology [17,18], and, just recently, a statement from the European professional societies on patient shielding was issued in which the recommendation was not to apply gonad shielding [19]. The Swedish Radiation Safety Authority has not yet changes their recommendations accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…This estimation allowed us to improve the radiation protection advice in cases where other protection may not be available or cannot be employed. Moreover, the use of radiation protection means for the patient has recently been re-evaluated and its use may even increase the dose to the patient and personnel, especially in complex procedures such as the interventional ones [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini karena pemeriksaan PCI dilakukan dengan menggunakan fluoroskopi dengan durasi fluorotime yang relatif lama. Dengan meluasnya radiologi intervensi dan potensi resiko radiasi yang besar dalam intervensi maka staf dan pasien di fasilitas radiologi intervensi memerlukan sistem proteksi radiasi yang sesuai (Maslebu et al, 2017;Samara et al, 2022;.…”
Section: Latar Belakangunclassified
“…Nilai DRL Nasional ditentukan pada nilai kuartil 3 (75 persentil) dari data sebaran dosis yang didapat dari fasilitas (K. L. Lee et al, 2020). Indikator Dosis radiasi yang dapat mendeskripsikan DRL pada fluoroskopi konvensional dan intervensional itu berupa DAP atau KAP (Gy.cm 2 ) atau Peak Skin Dose (mGy) atau laju kerma udara (mGy) (MILLER et al, 2021;Samara et al, 2022) . dan untuk nilai DRL Air Kerma bernilai 906 mGy (Schegerer et al, 2019).…”
Section: Latar Belakangunclassified